Nagranie prywatne jako dowód w sprawie karnej w świetle nowelizacji k.p.k. - Leśniewski, Kamil (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2015)
Rapid technological development has provided us with new efficient tools that we should not hesitate to use. In the last two decades we have seen technical revolution around us. Nevertheless, criminal procedure does not follow that change – saving evidence law. The article is focused on application of private recordings in Polish criminal procedure, with particular emphasis on its value as an evidence. The paper analyses practical problems related to the issue. The author presents different definitions of private evidence and private recording. The findings and conclusions represented in the author’s analysis show that the issue of private recording is very vital and has to be examined profoundly. Changes, that are shown in the article were introduced on 1st of July 2015, had been estimated as a huge step in “releasing” private evidence. The author pays attention to potential difficulties in interpretation of the new regulations.